2021
DOI: 10.1002/ajmg.b.32873
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study and polygenic risk score analysis for hearing measures in children

Abstract: An efficient auditory system contributes to cognitive and psychosocial development. A right ear advantage in hearing thresholds (HTs) has been described in adults and atypical patterns of left/right hearing threshold asymmetry (HTA) have been described for psychiatric and neurodevelopmental conditions. Previous genome-wide association studies (GWASs) on HT have mainly been conducted in elderly participants whose hearing is more likely to be affected by external environmental factors. Here, we investigated HT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
2
4
0
Order By: Relevance
“…Our self-reported dyslexia diagnosis binary trait showed strong negative genetic correlations with quantitative reading and spelling measures, supporting the validity of this measure in the 23andMe cohort, and suggesting that reading skills and disorder are not qualitatively distinct. The positive genetic correlation between hearing difficulties and dyslexia is consistent with genetic correlations reported for childhood reading skill 42 , suggesting that hearing problems at an early age could affect acquisition of phonological processing skills.…”
Section: Discussionsupporting
confidence: 82%
“…Our self-reported dyslexia diagnosis binary trait showed strong negative genetic correlations with quantitative reading and spelling measures, supporting the validity of this measure in the 23andMe cohort, and suggesting that reading skills and disorder are not qualitatively distinct. The positive genetic correlation between hearing difficulties and dyslexia is consistent with genetic correlations reported for childhood reading skill 42 , suggesting that hearing problems at an early age could affect acquisition of phonological processing skills.…”
Section: Discussionsupporting
confidence: 82%
“…Next, the Enhancing Neuro Imaging Genetics through Meta-Analysis (ENIGMA) consortium estimated a total of 63 traits with significant genetic correlates with dyslexia. The ENIGMA Consortium in a study has identified a positive genetic correlation between hearing difficulties and dyslexia, which is consistent with the genetic correlations reported for childhood reading ability, and which suggests that hearing problems at an early age could influence the acquisition of phonological processing skills [ 34 ]. Another example of a genetic correlation with dyslexia involves equal use of the hands, but not left-handed, supporting theories linking ambidexterity and dyslexia [ 35 ].…”
Section: Introductionsupporting
confidence: 59%
“…The association between hearing impairment and ADHD may be explained in several ways. First, specific genes were shown to be involved in both ADHD and hearing impairment (22). Second, compromised communication abilities negatively affect behavior and are associated with an increased risk for mental health disorders such as ADHD (10,14,23).…”
Section: Discussionmentioning
confidence: 99%